(untitled) (Journal of Computational Mathematics, 1984)
The estimation for solutions for the ill-posed Cauchy problems of the differential equation du(t)dt=A(t)u(t)+N(t)u(t),t(0,1) is discussed, where A(t) is a 2-nd order p.d.o. and N(t) is a uniformly bounded h-›H linear operator. Two estimates of ||u(t)|| are obtained.